Normative and functional intergenerational solidarity in Lithuania - Kraniauskienė, Sigita (Sociologija. Mintis ir veiksmas, 2013)
Current discussions in European countries about welfare policy focus on the issue how rapid social changes undermine intergenerational solidarity as a basic precondition of personal wellbeing. Therefore, intergenerational solidarity becomes a very important research area to explore several issues: (1) functional solidarity, or how exchanges of mutual assistance and support are organized among different generations within family; (2) normative solidarity, or how attitudes of familism/defamilism strengthen/weaken reciprocal support of adult children and their parents and what are expectations towards state’s support for family. The article is a study about social attitudes concerning various welfare regimes, normative and functional solidarity in Lithuanian families. The empirical data is taken from the Generation and Gender Program survey done in Lithuania in 2009. In our analysis of functional intergenerational solidarity we cover three areas of mutual assistance: emotional support, material or financial support, and assistance in taking care of dependent family members – children and elders. The issue of normative solidarity in Lithuania is also explored within the international context and how attitudes about intergenerational solidarity might be interpreted as a functioning social norm.